SISTEM MONITORING LAPORAN HARIAN AVIATION SECURITY BANDARA SULTAN SYARIF KASIM II BERBASIS ANDROID - Bambang Kurniawan; Muhammad Khaibar Putra Adithia; Septian Simatupang (Indonesian Journal of Thousand Literacies, 2023)
SSK2 Airport assigns basic duties to AVSEC officers. In performing their duties in accordance with the SOP, officers need to make daily reports that have been done every day. The process of monitoring the daily report of officers is currently still using "WhatsApp" technology, each officer submits his daily report through the WhatsApp Group media. But the reporting activity is still running less effectively because of the limited features provided by WhatsApp. Based on the description stated above, the author will raise the title of the study with the title "Monitoring System Of Daily Aviation Security Report sultan Syarif Kasim II Based On Android". With the daily report monitoring system, aviation security officers can conduct reporting activities through a system that has been integrated with the database. This system can be accessed at any time, and the possibility of loss and damage to daily report data is less because the data is stored offline in the system database. The research method used in this study is the waterfall method. Waterfall is the method most often used for system development, the system development model that is linear is the process from the initial stage to the final stage is done in sequence and will not continue the next stage before the previous stage is completed. The Daily Report Monitoring System of Aviation Security SSK II Pekanbaru Airport Based on Android is made in two platforms, namely Android and Website. The Android platform will be used by airport officials to report daily reports. While the website platform is used by admins and service heads to monitor daily reports of aviation security. Based on the results of tests conducted using the Blackbox testing method, the Daily Report Monitoring System of Aviation Security SSK II Pekanbaru Airport Based android can work well.